THE CONSTITUTIONAL RATIONALIZATION OF THE SEPARATION OF POWERS: THE CASE OF SERBIA - Pejić, Irena R (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2020)
Abstract: The main goal of this paper is to analyze the modalities of the separation of powers in the constitutional state. The starting point is that “pure” forms of separation of powers no longer exist even in traditional constitutional states, whereas in the so-called new democracies the practice is focused on exploring ways of rationalizing the traditional form of parliamentarism. Hence, the semi-presidential system as a new form in the 20th century is proving to be a new platform upon which new modalities of the separation of powers are being built. After considering the theoretical framework of semi-presidentialism, the author focuses on the constitutional approach in the process of selecting the organizational model of the separation of powers. The central topic is the constitutional construction of the separation of powers in Serbia since 1990 and its development through two normative constructions. The last part of the paper highlights, in particular, the prospective of the national separation of powers framework and the possible mechanism for balancing two branches of political power.